A Method for Optimizing the Load Characteristic of Disc Cam-Follower Mechanisms With Oscillating Roller Followers - Xiao Zhenqian; Wang Wenge; Pan Yukang; Rao Xinghua (Jixie chuandong, 2016)
The large load torque fluctuation of disc cam mechanism with oscillating roller followers mainly affects the steady performance of servo motor in high-speed precision machinery.According to the load characteristic,a optimization method for reducing the mechanism overall load torque fluctuation is proposed by optimizing the resistance torque in the process of active parts and follower.This method is based on the cam curve motion law modulation method and particle swarm optimization algorithm,through generating new cam profile to complete the optimization process.The optimization of device is completed by applying this method on transfer mechanism in high speed packaging machinery.The simulation result shows that,the load fluctuation of device can be effectively reduceds.